Next-generation sequencing: what are the needs in routine clinical microbiology? A survey among clinicians involved in infectious diseases practice - Michel, Charlotte; Martin, Charlotte; Smeesters, Pierre; Goffard, Jean-Christophe; Demuyser, Thomas; Hallin, Marie (Frontiers in Medicine, 2023)
Background The translation of Next-Generation Sequencing (NGS) from research to clinical microbiology is increasing rapidly, but its integration into routine clinical care struggles to catch-up. A challenge for clinical laboratories is that the substantial investments made in the required technologies and resources must meet both current and forthcoming needs. Methods To get a clinical perspective of these needs, we have sent a survey to infectious diseases clinicians of five hospitals, covering the following topics: NGS knowledge, expected syndromes and patients foreseen to benefit from NGS, and expected impact on antimicrobial prescription. Results According to clinicians, benefits of NGS are mostly expected in neurological and respiratory infections diagnostics. Conclusion A better dialog between microbiologists and clinicians about hopes and limits of NGS in microbiology may help identifying key investments needed for clinical laboratories, today and tomorrow.